Radical technologies. The project of everyday life by Adam Greenfield - Alunni, Desirè (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
In this book, Tore attempts to provide a critical and detailed explanation of a whole series of technological innovations that over time have become essential elements of each individual’s life. To do so, he provides an excursus through the most innovative technologies that have become part of the social fabric, from the smartphone to artificial intelligence.